Neutralization Mechanisms in Protest-related Vandalism: Implications for Psycholinguistic Crisis Communication - Lyndardi, M. Agung (UI Scholars Hub, 2026)
Protest-related vandalism has become a recurring phenomenon in Indonesia’s democratic landscape, particularly during large-scale demonstrations involving students, labor groups, and civil society coalitions. Conventional legal approaches that define vandalism as a public-order violation are insufficient to explain why such actions persist, why they concentrate on symbolic state targets, and why participants frequently deny moral wrongdoing. This article analyzes protest-related vandalism in Indonesia through the framework of neutralization theory (Sykes & Matza, 1957), integrating perspectives from criminology, moral disengagement theory, collective action, political legitimacy, and public psycholinguistics. Using a structured literature review of international and Indonesian scholarship published between 1957 and 2024, this study demonstrates that denial of responsibility, denial of injury, denial of the victim, condemnation of condemners, and appeal to higher loyalties operate as cognitive mechanisms that justify vandalism during protest escalation. These mechanisms are reinforced by moralized grievances, low institutional trust, digital protest communication, and state responses to mass demonstrations. The article argues that crisis communication by state authorities functions as a psycholinguistic intervention that can either amplify or constrain neutralization processes. The findings offer criminologically grounded implications for developing de-escalatory communication strategies that reduce protest-related vandalism while maintaining democratic legitimacy in Indonesia.